1999
DOI: 10.1046/j.1523-1755.1999.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Strong association between malnutrition, inflammation, and atherosclerosis in chronic renal failure

Abstract: These results indicate that the rapidly developing atherosclerosis in advanced CRF appears to be caused by a synergism of different mechanisms, such as malnutrition, inflammation, oxidative stress, and genetic components. Apart from classic risk factors, low vitamin E levels and elevated CRP levels are associated with an increased intima-media area, whereas small molecular weight apo(a) isoforms and increased levels of oxLDL are associated with the presence of carotid plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
1,186
11
41

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,585 publications
(1,293 citation statements)
references
References 52 publications
55
1,186
11
41
Order By: Relevance
“…In patients receiving insulin therapy in the present study, insulin may have had a vasodilatory effect and therefore a renoprotective effect. In patients with renal failure, serum tumor necrosis factor-␣ (TNF-␣) concentration is reported to be increased and related to insulin resistance, malnutrition, and inflammation (25,26). Insulin resistance caused by TNF-␣ may be alleviated or partly overcome by exogenous insulin administration and may improve tissue metabolism, such as in the kidneys, possibly resulting in a renoprotective effect.…”
Section: Resultsmentioning
confidence: 99%
“…In patients receiving insulin therapy in the present study, insulin may have had a vasodilatory effect and therefore a renoprotective effect. In patients with renal failure, serum tumor necrosis factor-␣ (TNF-␣) concentration is reported to be increased and related to insulin resistance, malnutrition, and inflammation (25,26). Insulin resistance caused by TNF-␣ may be alleviated or partly overcome by exogenous insulin administration and may improve tissue metabolism, such as in the kidneys, possibly resulting in a renoprotective effect.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation is frequent among CKD patients and is a powerful predictor of mortality in dialysis patients (Zimmermann et al, 1999). It has been suggested that low clearance of CRP and cytokines, uremia itself, hypervolemia and the presence of comorbidities are possible causes for inducing the acute-phase reaction in dialysis patients (Stenvinkel and Yeun, 2004). We found that 43.6% of the patients (n ¼ 24) had CRP levels of 0.5 mg/dl or greater, a value considered indicative of an inflammatory condition.…”
Section: Discussionmentioning
confidence: 99%
“…Protein-energy malnutrition (PEM) is highly prevalent in end-stage renal disease (ESRD) and indices of malnutrition are powerful predictors of morbidity and mortality in this population (Lowrie & Lew, 1990;Ikizler & Hakim, 1996;Kopple et al, 1997;Stenvinkel et al, 1999). While there are possibly multiple factors that contribute to the development of PEM in ESRD patients, decreased protein and energy intake caused by anorexia is certainly an important one.…”
Section: Introductionmentioning
confidence: 99%